UTILIZATION OF NYPA FRUIT (Nypa fruticans) AS A NATURAL INGREDIENT IN THE PRODUCTION OF LIQUID BATH SOAP RICH IN VITAMIN C - Ikhsanul Khairi; Oki Juanta; Hafinuddin Hafinuddin; Uswatun Hasanah (Universitas Teuku Umar, 2025)
This research aims to utilize nipah fruit juice (Nypa fruticans) as a natural source of vitamin C in the production of liquid bath soap that is rich in vitamin C. This research was experimental using a Completely Randomized Design (CRD) with the treatment of nipah fruit juice concentration added to the liquid soap formulation, including 0%, 5%, 10%, and 15%. The resulting soap was tested for organoleptic characteristics, physical characteristics (pH value, foam stability, homogeneity) and chemical characteristics (vitamin C content). The results of the study showed that the addition of nipah fruit juice significantly affected the parameters of color, aroma, and vitamin C levels, but had no significant effect on foam stability and homogeneity. The highest color and aroma parameters were obtained in treatment P1, namely 5 (very much like) and 4 (like). However, in other treatments, the lowest value was still acceptable to the panelists, namely 3 (neutral). The highest vitamin C value was found in formulation P4 (15%), namely 3.282 mg/mL. The highest pH value of soap was obtained at P1 (0%) which was 5 and the lowest was obtained at P2 (5%), P3 (10%) and P4 (15%) which was 4. Foam stability in each treatment obtained a value of >95%. Based on the observed assessment parameters, the best formulation was obtained in treatment P4.